Analysis and attribution of trends in water levels in the Vietnamese Mekong Delta. Issue 6 (20th September 2015) - Fujihara, Y.; Hoshikawa, K.; Fujii, H.; Kotera, A.; Nagano, T.; Yokoyama, S.
Abstract: In the Vietnamese Mekong Delta (VMD), water levels at some stations have increased. However, the factors that cause this rise in the VMD have not been identified. We considered four factors that may have contributed to the water level rise: (1) increased runoff from upstream, (2) sea‐level rise, (3) land subsidence, and (4) decrease in flood mitigation function because of construction of high dykes. We analysed daily maximum and minimum water levels, and mean daily water levels from 24 monitoring stations from 1987 to 2006. Using daily and annual water level differences, we classified the delta into two groups: one is dominated by flows from upstream, while the other is tide dominated. We then tested the trends of annual maximum and minimum water levels using the Mann–Kendall test, and identified the slope of the trend using the method of Sen. The areas of dyke construction were estimated using the Enhanced Vegetation Index (EVI) and Land Surface Water Index (LSWI) from the Moderate Resolution Imaging Spectroradiometer (MODIS) data. Results show (1) river inflow has little impact on rising water levels in the VMD, (2) the influence of high dykes on water level rise could not be quantified in this study, and (3) both maximum and minimum water levels significantly increased in the tide‐dominated area. Trend of annual minimum water level can be considered as the sum sea‐level rise and land subsidence. Therefore, we attribute 6.05 mm year −1 (80%) to land subsidence and 1.42 mm year −1 (20%) to sea level rise, indicating that inundations have been severe in the VMD, caused primarily by land subsidence. Copyright © 2015 John Wiley & Sons, Ltd.